Current state of kidney utilization in multiorgan transplants. Issue 4 (August 2020) - Aziz, Hassan; Kim, Jim; Kwon, Yong Kyong
Abstract : Purpose of review: In the United States, the leading indication for kidney transplant is primary kidney dysfunction arising from chronic hypertension and diabetes. However, an increasing indication for kidney transplantation is secondary kidney dysfunction in the setting of another severe organ dysfunction, including pancreas, liver, heart, and lung disease. In these settings, multiorgan transplantation is now commonly performed. With the increasing number of multiorgan kidney transplants, an assessment of guidelines and trends for in multiorgan kidney is necessary. Recent findings: Although the utilization of kidney transplants in combined liver–kidney transplant was sharply rising, following the introduction of the 'safety net' policy, combined liver–kidney transplant numbers now remain stable. There is an increasing trend in the utilization of kidney transplantation in heart and lung transplantation. However, as these surgeries were historically uncommon, guidelines for patients who require simultaneous heart or lung transplants are limited and are often institution specific. Summary: Strict guidelines need to be established to assess candidacy for kidney transplantation in multiorgan failure patients, particularly for combined heart–kidney and lung–kidney patients.